Kinematical analysis of somersault with twist in men's vault: Focusing on the Lou Yun and Akopian motions - Lim, K.-C.; Park, H. S. (Korean Journal of Sport Biomechanics, 2016)
Objective: The aim of this study was to determine the kinematical characteristics of somersault with twist in the Lou Yun and Akopian motions and to provide useful information to gymnastic athletes in men's vault. Method: The study subjects were 12 male adult top athletes. After 12 trials (7 Lou Yun and 5 Akopian trials) filmed by using two digital high-speed camcorders set at 90 frames/sec, kinematical data were collected through the direct linear transformation (DLT) method. The mean differences in biomechanical variables were compared during the second flight upward phase. The kinematic characteristics of somersault with twist in the Lou Yun and Akopian motions were identified. Results: In Lou Yun motion, the vertical release velocity through horse breaking was not difficult to obtain, so the athletes had enough time to prepare for the twist. Therefore, the Lou Yun motion has an advantage to make a cat twist in the pike posture. In the Akopian motion, obtaining the horizontal velocity through horse pushing was so easy that the Akopian athletes attained a large angular impulse and angular momentum. Therefore, the Akopian motion has an advantage to making a tilt twist in the body tilting posture. Conclusion: This study suggests that gymnastic athletes should control their body segment movements in order to increase the twisting angular velocity of the whole body, which requires regulation of the longitudinal moment of inertia of the body. Moreover, athletes should prepare for the shoulder and hip twists early in order to make the landing position in advance.